Insects grow and change - Pascoe, Elaine; Kuhn, Dwight (Milwaukee : G. Stevens, 2002)
Briefly describes how such insects as a praying mantis, silkworm, and bumblebee grow from eggs and larvae to adults.
"A Springboards into Science series."
"Weekly Reader Seal of Approval"--Cover.
Includes bibliographical references (p. 23) and index.
3.6
K-3
K-3
Keywords: Insects -- Development -- Juvenile literature; Insects -- Growth -- Juvenile literature; Insects -- Development; Insects -- Growth; Insects